A világkép és a világszemlélet megkülönböztetése a valláspedagógiában - NÉMETH, Dávid (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Differentiating the World Picture and Worldview in Religious Education. In the field of practical theology from a Christian pedagogical perspective we have to make a clear distinction between world picture (describing empirical reality) and worldview (determining personal affection to the first one). While the science based world picture tends to be as objective representation of our actual world as is could be, the worldview is hermeneutical system based upon principles, ideas and values. In most cases, mixing up these two notions cause tensions between faith and natural science. In order to clarify some points of differentiation and also reference to each other, this study investigates the two notions in the context of religious education.